PEMANFAATAN APPSHEET UNTUK IMPLEMENTASI QR CODE PADA PENCATATAN PERKEMBANGAN SISWA TK BERBASIS MOBILE APPLICATION - Avorizano, Arry; Afnan Sabili, Dian Ainurrafik; Hasan, Firman Noor (ISTEK WIDURI, 2025)
The mobile application-based student progress recording application at RA Mutiara is a tool that can assist in managing student attendance and assessments, making academic data management easier. With this application, data processing becomes organized and easily accessible, the application can only be accessed by teachers. In designing the mobile application-based student progress recording application, we utilize QR Code technology as a tool to assist in student attendance and assessments. The application development is carried out using the waterfall method, which consists of five stages: needs analysis, application design, application development, and application testing. The software used in building this application includes AppSheet, Draw.io, Spreadsheet, and Google Chrome. In system testing, the method used is Black Box Testing. Based on the research results, a mobile application-based student progress recording application has been developed at RA Mutiara. From the results of the system testing questionnaire, data was obtained showing that 84.6% of the 3 users stated that the system is effective and suitable for implementation at RA Mutiara.